A New View of the T-Loop Junction: Implications for Self-Primed Telomere Extension, Expansion of Disease-Related Nucleotide Repeat Blocks, and Telomere Evolution - Tomaska, Lubomir; Nosek, Jozef; Kar, Anirban; Willcox, Smaranda; Griffith, Jack D. (Frontiers in Genetics, 2019)
Telomere loops (t-loops) are formed at the ends of chromosomes in species ranging from humans to worms, plants, and with genetic manipulation, some yeast. Recent in vitro studies demonstrated that transcription of telomeric DNA leads to highly efficient t-loop formation. It was also shown that both DNA termini are inserted into the preceding DNA to generate a highly stable t-loop junction. Furthermore, some telomeric RNA remains present at the junction, potentially acting as a plug to further protect and stabilize the t-loop. Modeling the loop junction reveals two mechanisms by which the canonical chromosomal replication factors could extend the telomere in the absence of telomerase. One mechanism would utilize the annealed 3' terminus as a de novo replication origin. In vitro evidence for the ability of the t-loop to prime telomere extension using the T7 replication factors is presented. A second mechanism would involve resolution of the Holliday junction present in the t-loop bubble by factors such as GEN1 to generate a rolling circle template at the extreme terminus of the telomere. This could lead to large expansions of the telomeric tract. Here, we propose that telomeres evolved as terminal elements containing long arrays of short nucleotide repeats due to the ability of such arrays to fold back into loops and self-prime their replicative extension. In this view, telomerase may have evolved later to provide a more precise mechanism of telomere maintenance. Both pathways have direct relevance to the alternative lengthening of telomeres (ALT) pathway. This view also provides a possible mechanism for the very large repeat expansions observed in nucleotide repeat diseases such as Fragile X syndrome, myotonic dystrophy, familial amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The evolution of telomeres is discussed in the framework of these models.